High-Pressure Supercritical CO2 Extracts of Ganoderma lucidum Fruiting Body and Their Anti-hepatoma Effect Associated With the Ras/Raf/MEK/ERK Signaling Pathway - Zhu, Liping; Wu, Min; Li, Peng; Zhou, Yanfei; Zhong, Jinyi; Zhang, Zhiqiang; Li, Ye; Yao, Weixi; Xu, Jianhua (Frontiers in Pharmacology, 2020)
As a noted medicinal mushroom, Ganoderma lucidum (G. lucidum) has been reported to have a number of pharmacological effects such as anti-tumor and liver protection. Compared with the common ethanol reflux method, supercritical CO2 extraction has obvious advantages in obtaining antitumor extracts from G. lucidum fruiting body such as short extraction time, low temperature and no solvent residue. However, Using high-pressure supercritical CO2 without entrainer to obtain the antitumor extracts from G. lucidum and studying their anti-hepatoma effect have not been reported. In this study, high-pressure supercritical CO2 extracts obtained under 65, 85 and 105 MPa pressure named as G65, G85, G105 respectively and ethanol reflux extract (GLE) were used to investigate their anti-hepatoma activity and the underlying molecular mechanism. The total triterpenoid content of G85 was significantly higher than that of G65 and GLE, but did not differ significantly from that of G105 by UV and high-performance liquid chromatography. GLE, G65 and G85 could inhibit cell proliferation, arrest cell cycle in G2/M phase, and induce apoptosis in two liver cancer cell lines (QGY7703 and SK-Hep1), of which G85 had the strongest effect. The results showed that the potency of their cytotoxicity of the high-pressure supercritical CO2 extracts on human hepatoma carcinoma cells in vitro was consistent with their total triterpenoid content. G85 exhibited significant anti-hepatoma effect with low toxicity In vivo. Further mechanistic investigation revealed that the anti-tumor effect of these extracts was associated with their inhibition of Ras/Raf/MEK/ERK signaling pathway. Our findings suggest that the high-pressure supercritical CO2 extraction of G. lucidum fruiting body can be used to obtain a triterpenoid-rich anti-tumor agent, which may have potential clinical significance for the treatment of human hepatoma.